Relationship between saving and investment in Malaysia and Singapore -implications for capital mobility / Nurbaya Ahmad (Faculty of Business and Management, 2006)
The objective of this study is to see the relationship between saving and investment and its implication for capital mobility in a country. The evidence of this relationship will focus on the sample of data obtained from Malaysia and Singapore. The data consists of annual data of saving rate and investment rate from 1955 to 2003. The methods used are simple regression analysis, ordinary least square (OLS) and Pearson-product-moment correlation coefficient to examine the relationship between saving and investment in the two countries. The results show that there is a high positive relationship between saving and investment in Malaysia and Singapore. It also shows that saving affe~t investment and vice-versa. Although both of the countries have different economic background, where Malaysia is a developing country and Singapore is a developed country, the result indicates that there is high capital mobility in both of the countries.